Radiative leptonic decay B → γℓνℓ with subleading power corrections - M. Beneke (Journal of High Energy Physics, 2018)
Abstract We reconsider the QCD predictions for the radiative decay B → γℓνℓ with an energetic photon in the final state by taking into account the 1/E γ , 1/m b power-suppressed hard-collinear and soft corrections from higher-twist B-meson light-cone distribution amplitudes (LCDAs). The soft contribution is estimated through a dispersion relation and light-cone QCD sum rules. The analysis of theoretical uncertainties and the dependence of the decay form factors on the leading-twist LCDA ϕ +(ω) shows that the latter dominates. The radiative leptonic decay is therefore well suited to constrain the parameters of ϕ +(ω), including the first inverse moment, 1/λ B , from the expected high-statistics data of the BELLE II experiment.